Sektor Perdagangan Kota Surabaya di Era Kompetisi Global - Nurul Istifadah, - (Ikatan Sarjana Ekonomi Indonesia (ISEI), 2017)
The trade sector provides the biggest contribution of the establishment of gross regional domestic product of Surabaya. The trade sector in Surabaya consists of trade between regions (between districts and between islands) and trade between countries (international trade). The trade contribution between regions is bigger than the international trade. Spacially the trade sector in Surabaya spreads throught districts. There are thirty-one districts in Surabaya. The study aims to analyse the performance of the trade sector in every districts and plan the strategy to improve the performance of the trade sector in Surabaya. An analysis instrument used is shift-share analysis. The research result indicated that the performance of the trade sector ini every district is different. Only six districts have the performance of trade sector are large. It means that the trade sector don’t spread in all districts. Futhermore, based on sectoral and special analysis, the formulations of development strategy of the trade sector in Surabaya are (a) improving access to export both between regents and international trade, (b) enhancing quantity and quality of infrastructure in trade sector, and (c) utilizing the comparative superiority of the trade sector to be the competitive superiority.